Force-controlled pose optimization and trajectory planning for chained Stewart platforms - Beach, Benjamin; Chapin, William; Chapin, Samantha; Hildebrand, Robert; Komendera, Erik (Frontiers in Mechanical Engineering, 2023)
We study optimization methods applied to minimizing forces for poses and movements of chained Stewart platforms (SPs) that we call an "Assembler" Robot. These chained SPs are parallel mechanisms that are stronger, stiffer, and more precise, on average, than their serial counterparts at the cost of a smaller range of motion. Linking these units in a series overcomes their individual limitations and yet maintains their truss-like rigidity, enabling their potential use for a variety of purposes. The assembler robot will be used in concert with several other types of robots to perform complex space missions. We develop algorithms and optimization models that can efficiently decide on favorable positions and movements that reduce forces loads on the robot and hence reducing wear on this machine. The objective of this research is to maneuver the interior plates of the Assembler such that the load forces distributed through the legs of each constituent SP are more even, allowing for a larger workspace and a greater overall payload capacity. The Assembler is designed to function in concert with several other robots for a variety of space missions. Our computations focus on assemblers with four chained SPs, but our methods apply to an arbitrary number of SPs, and can be extended to general over-actuated truss-like robot architectures.